Prosthodontic rehabilitation after traumatic anterior teeth and anodontia of mandibular right second premolar: a case report - Ike D. Habar; Muchammad Ardiansyah; Ervina S. Surya; Richard Tetelepta; Maqfirah Amiruddin; Meriyam Muchtar (Journal of Dentomaxillofacial Science, 2018)
Objective: The success of rehabilitation patients depends on strategic treatment planning and choice of most suitable treatment modality. In this case, a 20 years male, reported both the maxillary central incisors were found to be fractured, 1/3 and 2/3 apical of teeth. In mandiblecondition, second right premolar is anodontia.Methods: This case report describes technique in restoring an uncomplicated fractured maxillary anterior teeth in a young patient with laminate veneer porcelain restoration and post fiber post with core build-up resin followed by using of porcelain crown for traumatic tooth and single implant for treatment second right premolar ofmandible.Results: Porcelain veneers is a conservative method of restoring the appearance of discolored, pitted teeth, and teeth with diastema that provide extremely good esthetic results. Post and post-core systems are used to restore extensively damaged teeth. Implants are considered as a first treatment option to replace missing teeth due to the considerable advantages over the other available options.Conclusion: The ultimate goal of this case treatment is to restore natural esthetics, function, long term health and patient comfort.